2018
DOI: 10.4081/monaldi.2018.858
|View full text |Cite
|
Sign up to set email alerts
|

The measure of effectiveness of a short-term 2-week intensive Cardiac Rehabilitation program in decreasing levels of anxiety and depression

Abstract: Research on heart disease have found a strong and consistent evidence of association between some psychosocial risk factors, including depression, anxiety, self-efficacy, lack of social support and outcome of disease. Depression increases the risk of cardiac death and is highly predictive of reduced adherence to recommended treatments; anxiety appears to be linked to adverse cardiac outcomes. It was demonstrated that Cardiac Rehabilitation (CR) leads to substantial improvements and positive outcomes because co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…The psychotherapist has a specific training on group psychotherapy and on the management of groups of patients with physical diseases, in addition to the therapist there are also a nurse and a trainee psychologist. The psychological support group offers patients a space dedicated to reflection on their own disease, allowing them to share their deepest anxieties and to understand how to live with the disease (Caccamo et al, 2018 ). During the group meetings, patients meet other patients who lived similar experiences and this increases the perception of social support and the reassurance that comes with it (Yalom & Leszcz, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The psychotherapist has a specific training on group psychotherapy and on the management of groups of patients with physical diseases, in addition to the therapist there are also a nurse and a trainee psychologist. The psychological support group offers patients a space dedicated to reflection on their own disease, allowing them to share their deepest anxieties and to understand how to live with the disease (Caccamo et al, 2018 ). During the group meetings, patients meet other patients who lived similar experiences and this increases the perception of social support and the reassurance that comes with it (Yalom & Leszcz, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies show the effectiveness of psychological support group treatment in cardiac patients (Caccamo et al, 2018 ). Group treatment not only allows sharing problems, including interpersonal conflicts, life transitions concerns and grief but it also addresses social isolation, a factor that was associated with an increased mortality and morbidity in some studies of patients with post-acute or chronic heart disease (Rutledge, Redwine, Linke, & Mills, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that ICR performs better than TCR for psychological health and weight loss, which can be attributed to ICR robust nonexercise components, such as a plant-based diet, relaxation techniques as well as emotional support of 1-hr each twice a week for 9 wk 2,27. Conversely, TCR patients achieved higher improvement in CRF compared with ICR patients, which is important as each MET improvement is associated with >10% reduction in long-term mortality risk 16,28–31.…”
Section: Discussionmentioning
confidence: 78%
“…Nonetheless, given that this was a feasibility study, future research with a larger number of participants and with full randomization to the experimental and control conditions should replicate the proposed design to test if further support can be provided to the results obtained. Given that rehabilitation interventions with social support have been found to be very helpful for cardiac patients [63] and could be carried out in a group format, we hypothesize that the efficacy of interventions developed in any future study would be stronger in a group format than in an individual format.…”
Section: Limitations and Future Researchmentioning
confidence: 99%